(untitled) (Journal of Plant Disease Sciences, 2017)
Integrated pest management special (IPMs) trial was conducted on three farmers fieldbyAgriculture Research Station, Sakoli, Dist. Bhandara, during , Kharif 2015, with an objective to manage insects, diseases and weeds in rice crop in a holistic and participatory manner. The results showed that the reduced incidence of gall midge and stems borer and low severity of sheath rot disease were noticed in IPM plots. Weed population and weed biomass were considerably reduced in IPM plots as compared to farmers practices. Grain yield was high in IPM as compared to farmers practice. Similarly, BC ratio was high in IPM than farmers practices.